2019
DOI: 10.1152/physiolgenomics.00039.2019
|View full text |Cite
|
Sign up to set email alerts
|

Heat stress negatively affects the transcriptome related to overall metabolism and milk protein synthesis in mammary tissue of midlactating dairy cows

Abstract: Inadequate dry matter intake only partially accounts for the decrease in milk protein synthesis during heat stress (HS) in dairy cows. Our hypothesis is that reduced milk protein synthesis during HS in dairy cows is also caused by biological changes within the mammary gland. The objective of this study was to assess the hypothesis via RNA-Seq analysis of mammary tissue. Herein, four dairy cows were used in a crossover design where HS was induced for 9 days in environmental chambers. There was a 30-day washout … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 58 publications
(106 reference statements)
1
30
3
Order By: Relevance
“…Alterations in lipid profile is considered as a valid indicator of stress [20,21]. For instance, hypocholesterolemia is an obvious metabolic sign for exposure to stressful situations as cholesterol requirement increases to support the biosynthesis of stress hormones and the production and functions of new cells participate in host defense and tissue repair [22].…”
Section: Introductionmentioning
confidence: 99%
“…Alterations in lipid profile is considered as a valid indicator of stress [20,21]. For instance, hypocholesterolemia is an obvious metabolic sign for exposure to stressful situations as cholesterol requirement increases to support the biosynthesis of stress hormones and the production and functions of new cells participate in host defense and tissue repair [22].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, in the cow, heat stress decreases mRNA expression of genes involved in production of key milk proteins (casein and lactalbumin) and transport of amino acids and glucose (Gao et al, 2019) when compared to that observed in pair-fed cows. In cows, heat exposure also appears to limit the ability of the mammary gland to mobilize fatty acids from triglycerides and catabolize those fatty acid through β-oxidation (Adin et al, 2009; Gao et al, 2019). Accordingly, depressed mammary function appears to be a direct response to heat and may be a result of limited metabolite flux.…”
Section: Discussionmentioning
confidence: 92%
“…Five cows were randomly selected from each treatment for liver tissue collection. The biopsy was conducted at the end of the 14 weeks as described by Gao et al (2019) and Bu et al (2017) [49,50]. Tissue samples were washed with PBS buffer prepared using RNAase-free water, and then stored in liquid nitrogen immediately until RNA extraction.…”
Section: Methods Experiments Animals and Managementmentioning
confidence: 99%